2021
DOI: 10.3389/fmicb.2021.635208
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights Into the Pathogenicity of a Novel Biofilm-Forming Enterococcus sp. Bacteria (Enterococcus lacertideformus) Identified in Reptiles

Abstract: Whole genome analysis of a novel species of enterococci, Enterococcus lacertideformus, causing multi-systemic and invariably fatal disease in critically endangered Christmas Island reptiles was undertaken to determine the genetic elements and potential mechanisms conferring its pathogenic nature, biofilm-forming capabilities, immune recognition avoidance, and inability to grow in vitro. Comparative genomic analyses with related and clinically significant enterococci were further undertaken to infer the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Moreover, unique genes epsM and epsL coding for putative acetyltransferase and sugar transferase, respectively, were detected. They are involved in the production of the exopolysaccharide (EPS) component of the extracellular matrix during biofilm formation (Agius et al, 2021 ). Gene cbh_2 , choloylglycine hydrolyse, catalyzes the de-conjugation of bile acids (Chand et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, unique genes epsM and epsL coding for putative acetyltransferase and sugar transferase, respectively, were detected. They are involved in the production of the exopolysaccharide (EPS) component of the extracellular matrix during biofilm formation (Agius et al, 2021 ). Gene cbh_2 , choloylglycine hydrolyse, catalyzes the de-conjugation of bile acids (Chand et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The treatments administered during the trial were chosen based on one or more of the following criteria: efficacy against Gram positive bacteria, ability to penetrate biofilms, therapeutic index, previous use in reptiles, capacity to administer via the oral route, and susceptibility to E. lacertideformus and other species of enterococci. A screen of the E. lacertideformus genome for antimicrobial resistance genes in a previous study revealed a resistance profile only to the antibiotics trimethoprim, tetracycline, streptothricin, and bacitracin 7 .…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, understanding the modes of transmission, clinical course of infection, and susceptibility of E. lacertideformus to antimicrobial treatments are critically important to inform disease control and management. Based on a recent metagenomics study 7 , it appears that E. lacertideformus has limited antibiotic resistance and is likely susceptible to fluoroquinolones, macrolides, broad-spectrum penicillins, and rifamycins, antimicrobials that are often effective against other enterococci and have the added advantage of high penetrating capacity of biofilms 8 , 9 . These antibiotics have also been shown to be safe when administered to reptiles and can be given orally, which is a significant advantage when treating reptiles as small as two grams.…”
Section: Introductionmentioning
confidence: 99%
“…We performed PCR amplification and Sanger sequencing of an approximately 1,400 base pair (bp) portion of the 16S SSU gene (GenBank accession number ON017515) on mass material from the index case using previously described methods (Schuurman et al 2004). Molecular analysis revealed 100% sequence identity to Enterococcus lacertideformus, a bacterium first observed in 2014 as the cause of similar lesions in multiple lizard species from Christmas Island, an Australian territory in the Indian Ocean (Rose et al 2017;Agius et al 2021). For further comparison, primers were designed to amplify the ITS region of the Enterococcus genome (Enter-o10F: 5 0 -TCAAAGATGCTGGGTTCCCC-3 0 and Entero553R: 5 0 -TGGGGTGAAGTCG-TAACAAGG-3 0 ) from mass material of 3/6 anoles, resulting in a 482-bp amplicon after primer editing that also exhibited 100% sequence identity to E. lacertideformus (Gen-Bank ON032371).…”
mentioning
confidence: 96%